Simulations of a kinetic plasma instability in streamers of transient luminous events - Jujeczko, P.; Błęcki, J.; Mizerski, K.A. (Archives of Mechanics, 2024)
We have supplemented the Particle-In-Cell code SMILEI with the module for collisions between charged and neutral particles. The code has been evaluated and used for the examination of the nonlinear stability and dynamics of plasma in conditions of Transient Luminous Events. The linear kinetic dissipative filamentation instability of current-carrying weakly-ionized plasma, identified in J. Błecki and K. Mizerski [Archives of Mechanics, 70, 535–550, 2018], was simulated. This instability did not occur in our simulations due to an early onset of nonlinear effects. This means that the time scales of the development of nonlinear effects are much shorter than the time scale of the linear dissipative instability.